Guideline to Gadget Usage for children: An Infographic Method - Hon, Kai Yee; Chua, Bee Seok; Yap, Chin Choo *; Gan Su Wan, (Universiti Malaysia Sabah Press, 2023)
“Guideline to Gadget Usage for children: An Infographic Method” is a book that helps the new millennium parents to reduce their children’s screen time by using the infographic method. It is affirmative easy to understand the content of the book with a vast number of illustrations and graphics. Besides, this book consists of four modules, which serve as a reference point for monitoring the children’s screen time, understanding the importance of parental rules and how to enforce the rules by following the guidelines. May this book help the parents and children on using the gadget effectively and together we combat the cyberbully issues and mental health problems among children.